Evaluation of the project to develop an information system for promoting community health - Jaidee, Patchana Hengboriboonpong; Junphum, Sirichai; Assawamaitree, Supattra; Na Phuket, Nisa Rattanadilok; Sittisaman, Nattakarn; Chaoniyom, Wanasara (International Journal of Public Health Science (IJPHS), 2025)
This study aimed to evaluate the Thailand Community Network Appraisal Program (TCNAP) during 2020-2022, utilizing a developmental evaluation framework based on the CIPP model. Data collection employed a mixed methods approach. Methods included in-depth interviews and focus group discussions with 204 representatives from the Healthy Community Strengthening Office under the Thai Health Promotion Foundation (Thai Health), the Research and Development Community Health System Center, the Center of Community Database Management, and the Regional Center of Academic Support for Network Management. Quantitative data were collected through online surveys assessing the effectiveness of the TCNAP project from 376 delegates of the co-creation livable community network. Descriptive statistics were used for quantitative data analysis, while thematic and content analysis were applied for qualitative data. Results indicated that the project network expressed high satisfaction with the database usage, with a mean score of 3.99±0.76. It was observed that 8 out of 10 indicators successfully achieved their objectives. Additionally, the pragmatic utility of information derived from TCNAP was evident in formulating local development plans and garnering external support for enhancing community health and quality of life. This commitment to evidence-based practice is encapsulated by the phrase “Data equals stability.” However, sustaining the implementation of the TCNAP project posed significant challenges. Proposed developmental strategies include organizing knowledge exchange activities, improving data collection tools and formats, and providing budgetary support tailored to the area context. Additionally, enhancing the operational system of TCNAP is crucial to ensure stability, convenience, efficiency, and adaptability for both current and future use.